Data resource profile: Norwegian Databases for Drug Utilization and Pharmacoepidemiology - Hilchen Thode Sommerschild; Christian Lie Berg; Christian Jonasson; Kari Jansdotter Husabø; Mohammad Nouri Sharikabad (Norsk Forening for Epidemiologi, 2021)
In this article we aim to give researchers and other users of drug utilization data a current overview of the twonationwide Norwegian drug databases located at the Norwegian Institute of Public Health (NIPH), withreference to some historical background. The first database, "The Norwegian Drug Wholesales Statistics",dating back to 1974, provides total sale figures of all medicines on the market. The second database, "TheNorwegian Prescription Database" (NorPD), dates back to 2004 and covers prescription drugs dispensed bypharmacies. This database will be modernized during 2021 and renamed ("The Norwegian Prescribed DrugRegistry", name not finally decided), and all historical data will be migrated to the modernized registry. In thefuture, the most valuable add-on to the modernized prescription database will be individual level data fromin-patients in hospitals and health care institutions, and the possibility to obtain aggregated data from eachinstitution. Together, the two nationwide databases will continue to be the cornerstones of drug utilization data in Norway and should be used more extensively to improve health to the best for individuals and society. Development in national e-health programs will play a key role in providing easier and less time-consuming access to data and improve conditions for linkage of drug data to other health registries in the near future.